A systematic dry-needling treatment to support recovery posttraining for division i ice hockey athletes: an exploration case series - Brewster, B. D.; Snyder Valier, A. R.; Falsone, S. (Journal of Athletic Training, 2022)
Context For this case series, 4 student-athletes (age range = 20-22 years) participating in National Collegiate Athletic Association Division I ice hockey served as cases. They were free of injury and participated in all team activities without restrictions.